IMPLEMENTASI KEGIATAN PENDIDIKAN DAN PELATIHAN DASAR DALAM MENGEMBANGKAN PERILAKU SOSIAL SANTRI - Diana, Dian; Waluya, Bagja (Universitas Pendidikan Indonesia, 2017)
Considerable attention to the development of social behavior shown by Institutions of Pesantren Daarut Tauhid, one of them in basic training activities aiming to shape basic character (Good and Strong), which are translated into social behavior. In this research, researchers used a qualitative research method with a case study approach. For researchers used data collection techniques of observation, interviews, and documentary. The results showed that the activities carried out for seven days and is mandatory for new students with a mechanism for the delivery of material good in theory, practice and extracting wisdom. Competence trainers involved in the activities of basic training is that the coach who had previously followed the coach education establishment (diktuktih). Through a spiritual approach was played, as for the development of social behavior that is perceived students in activities This basic training is that it can regulate and control the behavior of students, foster sensitive and care for others, creates a sense of gratitude that high because of the existence in nature which is too difficult, and feel the existence of God's help to face the activities previously felt unable to do.